Alterações cognitivas pós infecção pelo COVID-19 em profissionais de enfermagem que atuaram na rede pública de saúde de Uberlândia-MG entre os anos de 2020 a 2023 - Corrêa, Marcos Antônio (2024)
The present study aims to understand the impacts of COVID-19 on the lives and work of nursing professionals in the municipal public network of Uberlândia. The article focuses on analyzing the sociodemographic aspects, working conditions, experience with the disease, and behavioral changes experienced by these professionals during the pandemic. To carry out the evaluation, data were collected from professionals who worked in the care of health services in the public network of the municipality of Uberlândia, Primary Care, Secondary Care and Tertiary Care during the pandemic between the years 2020 and 2023. The selection of participants was made through sample calculation, based on the number of nursing professionals that made up the effective number of employees of the public network in the period, 1,852 professionals. The results revealed that nursing professionals who contracted COVID-19 showed several behavioral effects after recovering from the infection. Among the main ones, it presents sociodemographic data of the participants, describes the distribution of professionals by workplace, analyzes the professionals' working time, explores the changes in the position and work structure after the COVID-19 infection, and discusses the challenges of the pandemic for nursing professionals.